What happened from 2001 to 2011 in Melbourne? Compactness versus sprawl. (December 2015) - Rahnam, Mohammad Rahim; Wyatt, Ray; Heydari, Akbar
Highlights: We examine what happen in Melbourne between 2001 and 2011 about its urban growth. We calculated about 78 variables by linear regression, Neural Network and ArcGIS. Attention to Strategic planning will increase the compactness of Melbourne. Abstract: The main objective of this article is measuring the relationship and spatial changes of the income, population, use the car to go to the workplace, employment and distance from the city center of Melbourne from 2001 to 2011. In order to, calculated the change of mentioned variables in 78 statistical units (SU) based on Australian Bureau of Statistics (ABS) by multiple, linear regression and Neural Network in Matlab and ArcGIS software. Results showed that the overall population growth in this period was equal to 14.5%. Also average growth was 7.4%. In order to, the average income change, median employment change and ratio of car usage were respectively 57.7%, 1.19% and 12.43%. Over the period (2006–2011) the car usage to work has decreased from 67.02% to 66.31% too. Compacting Melbourne, need not only employment, but also providing other facilities for stabilizing the population. The results of this research show that in spite of a 10-year strategic plan focused on the compactness of Melbourne, efforts have not been successful. Finally, presented some solve ways using strategic plan to more compactness of Melbourne in the future.